Kesantunan Berbahasa dalam Bahasa Bali oleh Selebgram pada Media Sosial Instagram - Anak Agung Istri Manik Warmadewi; Anak Agung Gede Suarjaya; I.G.A.A. Dian Susanthi; Ni Luh Gede Mas Antartika Dewi Artana (LINGUA : Jurnal Bahasa, Sastra, dan Pengajarannya, 2021)
Many studies related to language politeness have been carried out. However, research related to politeness in Balinese is still very rare. There is a phenomenon of Instagram celebrities or celebrities that are currently on the rise, so that the existence of the Balinese language as one of Balinese local wisdom can be maintained, especially among young people who are indeed the most users of Instagram social media. This study uses the theory presented by Leech to answer questions about a form of politeness in the Balinese language by Balinese celebrities. The purpose of this research is to describe politeness in the Balinese language which is carried out by Balinese celebrities. The celebrities used as data sources are @haipuja and @taksu.north.bali. The research was conducted using a qualitative method. The theory used was the theory presented by Leech. The result is found 5 forms of maxims in accordance with what was conveyed by Leech.